2022
DOI: 10.1002/dad2.12281
|View full text |Cite
|
Sign up to set email alerts
|

Endurance and gait speed relationships with mild cognitive impairment and dementia

Abstract: Introduction Slower mobility is associated with mild cognitive impairment (MCI) and dementia. We examined the interaction of endurance with gait speed on prevalent MCI and dementia. Methods Cross‐sectional multinomial regression in the ARIC cohort (n = 2844 participants; 71 to 94 years; 44% men; 18% Black persons) with cognitive status (normal/MCI/dementia), 4 m gait speed, and endurance (2 minute walk [2MW]). Results Faster gait speed (up to but not above 1 m/s) and better 2MW were separately associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Firstly, the receiver operating characteristic (ROC) curve was constructed and the areas under the curves (AUCs) were compared amongst different models. Secondly, using > 5% as the threshold for the group at high risk to develop dementia in 10 years [ 29 ], categorical net reclassification improvement (NRI) was estimated for the added value of selected metabolomic biomarkers for risk stratification over conventional risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the receiver operating characteristic (ROC) curve was constructed and the areas under the curves (AUCs) were compared amongst different models. Secondly, using > 5% as the threshold for the group at high risk to develop dementia in 10 years [ 29 ], categorical net reclassification improvement (NRI) was estimated for the added value of selected metabolomic biomarkers for risk stratification over conventional risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…Impairments in multiple cognitive domains in older adults due to various underlying pathologies (ranging from the effects of aging per se to Alzheimer's disease) were shown to strongly associate with complex alterations in gait (Goldberger et al, 2002;Owings and Grabiner, 2004;Hausdorff, 2005;Hollman et al, 2007;Brach et al, 2008Brach et al, , 2010Montero-Odasso et al, 2014;Rosso et al, 2015;Sorond et al, 2015;Cohen et al, 2016;Moon et al, 2016;Hackett et al, 2018;Öhlin et al, 2020) shown to associate with multifaceted gait abnormalities, including slower speed and balance function (Bäzner et al, 2000;Baezner et al, 2008;de Laat et al, 2010;Choi et al, 2012;Smith et al, 2015;Kim et al, 2016;Pinter et al, 2017a,b;Su et al, 2022). In the past decade, advanced methods of gait research, including approaches to quantify variability and regularity/predictability/probability have been introduced to identify patients at risk for the development of cognitive impairment (Savica et al, 2017;Windham et al, 2022). Studies in preclinical models confirm that CSVD-related cognitive impairment is preceded by subclinical alterations in gait coordination, including increased gait variability, decreased symmetry and decreased orderliness and regularity (Toth et al, 2015;Tarantini et al, 2017;Nyul-Toth et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A Kinect v.2 camera (a depth camera from Microsoft corporation) was used to record the participants' gait while performing two different walking tests: a straight and a curved walking test. Each test covered a distance of 10 meters, a recognized standard for reliable gait assessment across populations, including MCI subjects [16][17][18]. For each participant, three trials were conducted on both straight and curved paths, with the mean of these trials calculated to ensure robust gait analysis.…”
Section: Gait Measurementmentioning
confidence: 99%